Control the normalized polarization ratio of a focal spot in speckle field formed by non-polarization-maintaining multimode fiber. (27th March 2019) - Fan, Weiru; Chen, Ziyang; Gezhi, Zhaxibamao; Chen, Li; Wang, Xiaoyan; Pu, Jixiong
Abstract: Due to the effects such as mode coupling, bending, mode dispersion, etc, a speckle pattern is generated by passing a coherent laser beam through a multimode fiber. For a non-polarization-maintaining multimode fiber, the randomization also occurs in the polarization distribution. Feedback-based wavefront shaping has been applied in modulating the speckle generated by a scattering medium. Based on the feedback-based wavefront shaping, we propose the combination method to modulate the normalized polarization ratio (NPR) of a focal spot in the speckle field formed by non-polarization-maintaining multimode fiber. The quantitative control of the NPR is achieved by amplitude modulation or phase modulation.